The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1590/0370-44672021750076
|View full text |Cite
|
Sign up to set email alerts
|

Development of innovation routes for iron ore using high intensity magnetic separators

Abstract: The mineral processing of low-grade iron ores commonly generates large volumes of slime, which are disposed as tailings. Modern mining requires strives to eliminate the use of tailings dams in a maximum effort to increase metallurgical recovery, the security and reduction of the operational cost. This research aims for the recovery of iron contained in the slime, which consists of a material with 38% Fe and <40 µm, originating from the desliming cyclones. Pilot tests were performed on the Wet High-Intensity Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Several authors have demonstrated a series of new technologies that could enhance magnetic separation processes through the development of new characterization techniques [27], equipment's [28][29][30][31][32][33][34] and the use of different matrices in high-intensity magnetic separation [35][36][37][38][39]. Such alternatives may result in significant gains in capacity, fines recovery, quality, and metallurgical recovery, as they make use of existing capacity and require low capital investment.…”
Section: Otimização Da Separação Magnética Da Hematita Contida No Pro...mentioning
confidence: 99%
“…Several authors have demonstrated a series of new technologies that could enhance magnetic separation processes through the development of new characterization techniques [27], equipment's [28][29][30][31][32][33][34] and the use of different matrices in high-intensity magnetic separation [35][36][37][38][39]. Such alternatives may result in significant gains in capacity, fines recovery, quality, and metallurgical recovery, as they make use of existing capacity and require low capital investment.…”
Section: Otimização Da Separação Magnética Da Hematita Contida No Pro...mentioning
confidence: 99%